Entraves à autonomia na formação de professores de língua inglesa - (:unkn) unknown (Universidade Estadual de Goiás, 2017)
This article intends to analyze the process of Educational Linguistic program which language teachers spend in a double degree course in Languages (Portuguese/English). According to Paiva (2009), about Foreign Language learning (hereafter FL), we cannot learn it if we just study in classes activity. Regarding that perspective, this study presents a participation of the students‟ analysis during his education program in the fourth year of the Language degree, observing classes and activities proposals in English Language IV (subject). The article aims at identifying some learning-teaching obstacles faced by undergraduate students and exploring suggests to help learners to develop autonomy as students and prepare then to be able to teach language in future. The nature of this study is qualitative/interpretive, following the references of Moita Lopes (1994) and Flick (2009). The study is based on observations of the English Language IV classes and interviews with those undergraduate students. Considering those observations is possible identify, in the first place, the profile of the students which is almost completed the career as English Teacher, think how important is innovative models of teacher training, considering nontraditional models of teaching. Keeping all these facts faced by English teachers in training it is important that teachers training occur based on critical and reflexive perspective and so that develop autonomy as students and as potential teachers.(LEFFA, 2001; FREIRE; LEFFA, 2013; PESSOA, 2011; PESSOA; BORELLI, 2011; TAVARES; ALARCÃO, 2001; FREIRE, 2009; STURM, 2011; MONTEIRO, 2011).
Keywords: Autonomia; Ensino-aprendizagem de línguas; Formação de professores; Autonomy; Learning-teaching languages; Teacher education; CIENCIAS HUMANAS::EDUCACAO; LETRAS::LINGUAS CLASSICAS